PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, OPINI AUDIT DAN REPUTASI AUDITOR TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Sektor Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2018 - 2021) - Hidayat, Aditya Wirananda; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
This study examines the influence of company size, profitability, solvency, audit opinion and auditor reputation on audit report lag This study has dependent variable named audit report lag and independent variables company size, profitability, solvency, audit opinion and auditor reputation. This study used secondary data derived from the financial statements of all companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The research sampling was carried out using purposive sampling method and has 52 samples for 4 consecutive years. This study used multiple linear regression analysis to test the hypothesis. The results of this study show that in the period before the Covid-19 pandemic, profitability and audit opinion had a negative and significant effect on audit report lag, while company size, solvency and auditor reputation had no effect on audit report lag. On the other hand, during the Covid-19 pandemic, solvency had a negative and significant effect on audit report lag, while company size, profitability, audit opinion and auditor reputation had no effect on audit report lag.